REGIONAL SPECIFICS OF THE DEVELOPMENT OF THE ENTREPRENEURIAL SECTOR IN GEORGIA - Irine Chanturidze (ეკონომიკური პროფილი)
In recent decades, the development of the entrepreneurial sector in Georgia has been characterized by contradictions between territorial units. Since this period, one of the main directions of economic reforms carried out in the country has been to overcome the negative tendencies in the territorial entities, resulting from the economic crisis, to maximize the potential of the regions, to transform all spheres of economic activity, taking into account their specific features. The presented article discusses the difficulties faced by the entrepreneurial sector after independence. The study focuses on the regional specifics of the development of the entrepreneurial sector in Georgia. Based on calculations, regional differences in various indicators are presented and conclusions are drawn.